Karakterisasi dan Potensi Ekstrak Daun Paitan (Tithonia diversifolia) sebagai Penolak Nyamuk Aedes aegypti - Dwi Wahyuni; Hari Untarto Swandono; Herlinda Mawardika; Mega Yuliya Prana (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
The paitan plant (Tithonia diversifolia) contains alkaloids, saponins, flavonoids, tannins and phenolics which have the potential to prevent Dengue Hemorrhagic Fever (DHF). This plant also has various insecticidal activities. In society, there are many mentions of the paitan plant, so people need to know the characteristics of this paitan plant. The aim of this research is to determine the morphological characterization and specific fragments of the paitan plant, as well as to determine the activity and effective concentration of the ethanol extract of paitan leaves as a repellent for the Aedes aegypti mosquito. Two types of methods were used, namely descriptive qualitative for observing morphology, specific fragments, pollen, and phytochemical screening, and experimental methods for mosquito repellent testing, and calculating the protective power of the ethanol extract of paitan leaves. The results obtained are flowers consisting of two shapes, namely ribbon flowers in the outer circle, infertile, and tube shapes in the inner circle. Stomata are anomocytic type, while trichomes are non-glandular multicellular type. Pollen characteristics, namely small size, colpate, number 3, aperture shaped trizonocolpate with echinate ornamentation. The screening results for the ethanol extract of paitan leaves were positive for containing metabolite compounds, such as flavonoids, alkaloids, tannins, saponins, terpenoids and phenolics. The results of the mosquito repellent test showed that the higher the concentration of the extract, the fewer mosquitoes that landed. Calculation of protective power shows that the most effective concentration in repelling mosquitoes is 15%, namely 93.64%. The conclusion is that paitan (Tithonia diversifolia) leaf extract has potential activity as a repellent against Aedes aegypti mosquitoes with the most effective concentration being 15%.